Stochastic optimization of strategic mine planning of a hypothetical copper deposit through a parametrizable algorithm (2016)
To perform a surface mine planning it is necessary to start from an initial evaluation of the mineral resource. The open pit schedule evaluation is a key step in the process of planning the extraction activities of a mining company. Traditional approaches applied to define the ultimate pit limit consider a single estimated model, which deviates from a real assessment of the mineral asset. Over the recent years, new approaches were proposed, so that the benefits of departing from deterministic world view, where every variable are static and modeled from an arithmetic average, to a stochastic evaluation which allows understanding the risk associated to the open pit long term mine planning. Exact optimization approaches were studied due the major roll of mine planning to financial analytics, however the implications associated with these methods are considered and a metaheuristic approach is proposed to solve the case of study.